أثر تواتر الري عند مستوى ثابت من التسميد المعدني على المواصفات الكمية والنوعيّة لتبغ الفيرجينيا - محمد, رامز (Latakia University Journal -Biological Sciences Series, 2016)
هدف هذا البحث إلى دراسة تأثير تواتر الري عند مستوى موحّد وملائم من العناصر الأساسة (N 75 , P 150 , K 125) على المركبات الكيميائية لورقة التبغ الجافة (سكريات ذائبة، نشا، نيكوتين، بروتين) ، وعلى بعض الأكاسيد المعدنية المهمة في ورقة التبغ الجافة (K2O, P2O5)، وعلى أيون الكلوريد، وعلى بعض الصفات الفيزيائية للورقة (معدل الاشتعال ، الكثافة الظاهرية ، السماكة) . وقد أظهرت النتائج ما يأتي: ـ أدى الري بفواصل زمنية قصيرة (خاصةً كل أسبوع) إلى إعطاء أعلى إنتاج (1228.7 كغ/دونم) وزن أخضر بالمتوسط ، (213.7 كغ/دونم) وزن جاف بالمتوسط ، ولم تتأثّر نسبة التصافي. ـ تحسّنت كذلك نوعية أوراق التبغ بتقصير فترات الري. ـ ازدادتْ سماكة الأوراق وتحسن معدل الاشتعال بتقصير الفترات الفاصلة بين الريات، وكانت الكثافة الظاهرية أعلى في رية الشاهد ، ولم تتأثر بتقصير فترات الري This work was directed to study the effect of frequentative irrigation at one suitable level of main elements (N 75 , P 150 , K 125) on the chemical composition related to quality of leaves (sugar, starch, chloride, metallic oxides like P2O5, K2O, nicotine, proteins) and also to study the same effect on some physical properties of leaf (burn rate , apparent density , thickness) . The results showed the following: - A short periods of irrigation (especially every week ) led to giving, clearly, higher production (1228.7 kg/d) green weight , (213.7 kg/d) dry weight, meanwhile, purity percentage did not effected . - Also improvement of the quality of leaves with shorten of irrigation periods. - Also, thickness of leaves increased and burn rate improved with shorten of irrigation periods , meanwhile the control sample had higher apparent density than others and did not affected with shorten of irrigation periods . .